Implementasi Metode Bercerita Dalam Membentuk Karakter Jujur Pada Anak Usia Dini - Karmila Wardani; Nur Kholik Afandi (Jurnal Warna : Pendidikan dan Pembelajaran Anak Usia Dini, 2023)
Developing honest character in children between the ages of 4 and 6 is very important as this period is known as the "golden age". However, few actually practice storytelling techniques. The purpose of this study is to find out how early childhood character is shaped by storytelling. This study examines how using a narrative approach to teach about the life of the apostle in group B, RA Darul Falah I Samarinda, can improve early childhood honesty. Classroom action research is the type of this study. As research techniques, observation, interviews, and documentation were used to collect qualitative descriptive data. According to the findings of the data analysis, 60% of the pre-action children reflected their honesty on average. Children's honesty increased to 75% as a result of the information generated by stage I data analysis. The results of stage I data analysis showed that the moral character of children who achieved BSB was 44% or 6 children, BSH was 2 children or 14%, MB was 4 children or 28%, and BB was 2 children or 14%. After following the same treatment in the second stage, 72% of children or 12 children got BSH results, 2 children got BSB 2 or 28% and children no longer got MB and BB. The proportion of stage 2 assessment increased to 85%. Based on the research findings above, it can be stated that the story approach can effectively improve the honesty of group B children, who are 5 to 6 years old and belong to RA Darul Falah I Samarinda. The findings of this study can be recommended for use in early childhood learning to improve children's honesty through the use of historical stories of prophets.